0751 Longitudinal Sleep Problem Trajectories And Child Functioning At Ages 10-11 Years. (12th April 2019) - Williamson, Ariel A; Mindell, Jodi A; Hiscock, Harriet; Quach, Jon
Abstract: Introduction: Although childhood sleep problems are associated with adverse outcomes, little is known about the impact of sleep problem trajectories over time on child functioning. This study examined whether distinct sleep problem trajectories from infancy through middle childhood are associated with variation in child psychosocial, behavioral, and academic functioning at ages 10-11 years. Methods: Data were from the first six waves of the Longitudinal Study of Australian Children - Birth Cohort (5, 107 children recruited at birth). Caregivers reported on child sleep problems at each time point. Child functional outcomes at ages 10-11 years included the caregiver- and teacher-reported Strengths and Difficulties Questionnaire (SDQ), the caregiver-reported Pediatric Quality of Life Questionnaire (Peds-QL), and the teacher-reported Academic Rating Scale (ARS; literacy/language and mathematics) and Approach to Learning. Sleep problem trajectories were used to predict these outcomes in regression models with covariates (child sex, indigenous status, and sleep behaviors). Results: Latent profile analysis identified five distinct sleep problem trajectories from ages 0-1 years to 10-11 years: persistent sleep problems through middle childhood (7.66% of the sample), limited infant/preschool sleep problems (9.03%), increased middle childhood sleep problems (17.02%), mild increases over time (14.43%), and no sleep problems (51.85%). Compared to those with no sleep problems, the persistent sleep problems and mild increases over time sleep problems trajectories were associated with impaired functioning across all outcomes. The limited infant/preschool trajectory was associated with poorer outcomes except for the language/literacy ARS. The increases in middle childhood group was only associated with poorer caregiver-reported PedsQL and SDQ scores. Those with persistent sleep problems had the greatest impairments, with moderate to large effect sizes (0.46 to 1.06). Conclusion: Distinct sleep problem trajectories predict child psychosocial, behavioral, and academic functioning at 10-11 years. Having persistent sleep problems over time is linked to having the greatest functional impairments in middle childhood, underscoring the importance of identifying and intervening on sleep problems early in childhood. Support (If Any): Sleep Research Society Foundation; National Institute of Child Health and Human Development (K23HD094905-01A1); National Health and Medical Research Council Practitioner Fellowship (1136222).